Using spray-dried microalgae as a natural coloring agent in chewing gum: effects on color, sensory, and textural properties - Palabiyik, Ibrahim; Durmaz, Yasar; Oner, Baris; Toker, Omer Said; Coksari, Gulay; Konar, Nevzat; Tamturk, Faruk (SPRINGER, 2018)
Chlorophyll-a and total carotenoid quantities of Isochrysis galbana and Nannochloropsis oculata biomass dried at different inlet temperatures (150-200 degrees C) using the spray dryer technique were investigated. The amounts of chlorophyll-a in I. galbana and N. oculata biomass were determined in the range of 7.775-11.377 mg g(-1) and 1.1411.836 mg g(-1), respectively. Total carotenoids were found as 1.984-3.373 mg g(-1) (dry biomass) for I. galbana and 0.3780.077 mg g(-1) (dry biomass) for N. oculata. Then, these biomasses were used at levels of 0.5% and 1% as natural green colorants in chewing gum, and color, texture, and sensory properties of chewing gums were investigated. The samples were identified as khaki or light khaki. L* value of the samples containing I. galbana species ranged from 42 to 53, a* value ranged from - 1.3 to - 2.88. b* value ranged from 11.5 to 15, and C* value ranged from 9.4 to 15.2, while L* values ranged from 55 to 65, a* value varied from - 0.03 to - 1.7. b* value varied from 15 to 18.2, and the C* value varied from 15 to 18.2 for N. oculata biomass. The highest cohesiveness value was found as 0.26 in the samples containing 1% I. galbana species dried at 180 degrees C. There were no alga tastes except for chewing gum containing 1% N. oculata dried at 150 degrees C.
Keywords: Confectionery; Chewing gum; Natural additive; Coloring agent; Drying; Nannaochloropsis oculata; Isochrysis galbana; Microalgae; FATTY-ACID-COMPOSITION; PORPHYRIDIUM-CRUENTUM; ISOCHRYSIS-GALBANA; NANNOCHLOROPSIS SP; MARINE MICROALGAE; NUTRITION; CULTURE; ALGAE; Biotechnology & Applied Microbiology; Marine & Freshwater Biology